Systemic hypertension in patients with glomerulonephritis - Corpa, Marcus V. N. [UNESP]; Soares, Vitor [UNESP] (Taylor & Francis, 2002)
Although systemic hypertension is very common in patients with glomerulonephritis there is a dispute if this alteration is consequence of the glomerulonephritis per se or is a consequence of the renal failure secondary to the glomerular lesion. With the aim to analyze the factors associated with systemic hypertension, 196 patients with different forms of nephritis were studied. The systemic arterial pressure was measured by standard sphygmomanometer, renal function was evaluated by the determination of the serum creatinine concentration or creatinine clearance. The diagnosis of the type of glomerulonephritis was made on the basis of an examination of kidney biopsy specimens. The prevalence of arterial hypertension among patients with glomerulonephritis was 62.7%. The hypertensive patients were older (hypertensive = 30.6 ± 12.8; normotensive = 25.4 ± 1.6 years; P = 0.03). The prevalence of arterial hypertension was lower in patients with minimal glomerular lesion (12.5%), though their ages were also lower (18.1 ± 3.6 and 29.1 ± 1.03 years; P = 0.03). Arterial hypertension did not correlate with the serum levels of creatinine and albumin; creatinine clearance and 24-h proteinuria. In conclusion: In the patients with glomerulonephritis, the presence of arterial hypertension was associated with a higher mean age whereas the intensity of proteinuria, the level of renal function or the type of glomerulonephritis was not different between the two groups.
Keywords: Arterial hypertension; Focal and segmental glomerulosclerosis; Glomerulonephritis; Lupus nephritis; Nephrotic syndrome; creatinine; biological marker; serum albumin; adolescent; adult; arterial pressure; creatinine clearance; female; glomerulonephritis; human; hypertension; kidney biopsy; kidney failure; major clinical study; male; nephrotic syndrome; prevalence; priority journal; proteinuria; risk factor; blood; blood pressure; clinical trial; comparative study; diastole; evaluation; metabolism; pathophysiology; physiology; systole; Adult; Biological Markers; Blood Pressure; Comparative Study; Creatinine; Diastole; Female; Human; Hypertension; Male; Nephrotic Syndrome; Prevalence; Risk Factors; Serum Albumin; Support, Non-U.S. Gov't; Systole; Humans